Maximizing Red Chili Yield through NPK Fertilizer and Agricultural Waste Biochar Utilization - Yohanes Parlindungan Situmeang; Made Suarta; Dewa Nyoman Adita (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2023)
This study aims to determine the effect of NPK combined with biochar from various agricultural wastes in increasing the growth and yield of red chili plants. The research method used was a Randomized Complete Block Design (RCBD) with a factorial pattern, involving two factors and three replications. The first factor is the NPK fertilizer dosage, comprising four levels: 0, 300, 600, and 900 kg ha-1. The second factor is the biochar treatment, consisting of four types: biochar from mangosteen skin, biochar from rambutan, biochar from coffee skin, and biochar from rice husk. The application of NPK fertilizer has a significant to very significant effect on all observed variables, except for intangible effects on variables such as stem diameter, root fresh weight, plant fresh weight, and root dry weight. The biochar treatment has no significant effect on all observed variables, except for fruit weight and fruit count, which show a significant effect. The interaction between NPK fertilizer and biochar has no significant effect on all observed variables, except for plant height, number of leaves, number of fruits, and fruit weight, which exhibit a significant to very significant effect. The highest fruit weight of 205.70 g was obtained from the interaction between a dosage of 900 kg ha-1 with biochar from coffee skin, showing an increase of 114.72% compared to the lowest treatment fruit weight obtained from the interaction between no NPK dosage and biochar from rambutan, which was 95.80 g.